Adsorption Equilibrium Isotherm Study of Gold Removal Using Regenerated Activated Carbon from Cyanidation Leachate - Abdul Rahim Liwang (Candela Edutech Indonesia, 2025)
Regenerated activated carbon is a type of activated carbon that is reused in adsorption processes after undergoing elution and regeneration. This study evaluates the adsorption performance of regenerated activated carbon compared to fresh activated carbon based on the Freundlich isotherm constant and adsorption heterogeneity. Adsorption experiments were carried out on gold-bearing cyanidation leach solutions with an initial gold concentration of 0.804 mg/L using various activated carbon dosages of 0.25 g/L, 0.50 g/L, 1.0 g/L, 2.0 g/L, 4.0 g/L, and 8.0 g/L. All other parameters affecting absorptivity were kept constant for each dosage, including an adsorbate volume of 0.5 L, free cyanide concentration of 200 mg/L, agitation speed of 150 rpm, contact time of 5 hours, ambient temperature, pH of 10.5, and activated carbon particle size between 1.18-2.36 mm. The results indicate that the Freundlich adsorption constant (Kf) of regenerated activated carbon was 1370 (log Kf = 3.1368), closely comparable to that of fresh activated carbon, which was 1632 (log Kf = 3.2127). The adsorption heterogeneity index (1/n) for regenerated activated carbon was 0.47, also like that of fresh activated carbon (0.46). The optimum dosage of regenerated activated carbon was found to be 4 g/L, yielding a gold adsorption efficiency of 98.7% with a relative activity of 100% compared to fresh carbon, and resulting in a low residual gold concentration of 0.011 mg/L